Biopolítica, población y control - Tejeda González, José Luis (2010)
Los estudios del poder han volteado hace tiempo a la biopolítica, vista como la intromisión e injerencia del poder y la política sobre la vida. Se da en positivo y en negativo. De ahí la discusión sobre el control social, como una expresión de la biopolítica moderna. La conexión entre biopolítica y población no es menos significativa que la manera cómo el poder administra y regula los nacimientos y la migración así como la calidad de vida de los conglomerados sociales
Studies on the power turned some time ago to biopolitics, seen as the interference of power and the politics in life. It is positive and negative. Hence the discussion about the social control as an expression of modern biopolitics. The connection between biopolitics and population is not less significant than how power manages and regulates the births and the migration as well as the quality of life of social conglomerates
Keywords: Biopolítica; Población; Control; Dominación; Cuerpo; Biopolitics; Population; Control; Domination; Body